An investigation of hearing impairment in de-novo Parkinson's disease patients: A preliminary study. Issue 8 (August 2015) - Pisani, Valerio; Sisto, Renata; Moleti, Arturo; Di Mauro, Roberta; Pisani, Antonio; Brusa, Livia; Altavista, Maria Concetta; Stanzione, Paolo; Di Girolamo, Stefano
Abstract Objective To investigate the peripheral auditory pathway in Parkinson's disease (PD) by using objective, quantitative and non-invasive audiological techniques, transient-evoked (TEOAE) and distortion product (DPOAE) otoacoustic emissions, in order to detect subclinical alterations of cochlear functioning and possible changes after dopaminergic stimulation. Methods We enrolled 11 untreated de-novo PD patients and 11 age and sex-matched healthy controls. Subjects underwent a routine audiological evaluation and otoacoustic emission recordings. The patients were then slowly-titrated to a stable dose of 100 mg levodopa four times in a day. A post-treatment assessment was made in order to detect significant changes in audiological responses. Finally, possible associations between clinical data and hearing results were also evaluated. Results At pure-tone audiometry, higher auditory threshold levels were observed in PD when compared to the controls. Moreover, DPOAE responses in PD patients were found low at almost all tested frequencies, suggesting subclinical cochlear damage. Interestingly, after dopaminergic treatment, a significant increase in DPOAE responses was detected. Notably, DPOAE dysfunction correlated with clinical severity, whereas high hearing thresholds appeared positively related with more prolonged disease duration. Conclusions Our findings demonstrate that otoacoustic emission recording and pure-tone audiometry reveal levodopa-sensitive cochlear dysfunction and hearing loss in PD. A parallel improvement in subjective motor symptoms and DPOAE objective responses could help clinicians in monitoring therapeutic responses and dynamic changes during the course of the disease.